Validated Risk Identification Tool for ICT in International Development Co‐operation Projects. Issue 1 (5th December 2017) - Kemppainen, Jyri; Mpogole, Hosea; Tedre, Matti; Chachage, Bukaza
Abstract: Literature shows that there are a number of different frameworks for managing international development co‐operation (IDC) projects. Those frameworks have their own strengths and weaknesses and they vary from being highly abstract to relatively practical. However, none of the frameworks provide help in situations where IT professionals are incapable to identify potential project risks when entering a new project milieu. The situation is common in the context of IDC projects. For this purpose, Kemppainen et al. (2012) designed a taxonomy‐based risk identification tool. The tool addresses potential risks by 55 quantified yes/no‐questions. The quantification specifies the significance of each issue to project success. The tool is aimed at guiding IT professionals, planners, donors, field staff, and other stakeholders to identify and mitigate potential threats that may materialize in an unfamiliar project context. The tool's questions were designed based on the literature analysis, their classification into five groups was derived from Tedre et al. (2011), and their taxonomy based scoring was derived from the researchers' own data. Hence, the tool lacked wider empirical evidence. This study validated the tool based on empirical data of a sample of 83 IT experts and IT department leaders from a number of organizations, institutes, universities and international development co‐operation projects in Tanzania. The mode value of the Likert‐scale questionnaire answers were used to adjust the question‐scoring scheme, and reliability analysis were conducted for testing internal consistency of the question groups' questions. Systematic reorganization of the questions with reliability analysis and content considerations led to three distinct question groups instead of the five original ones. In addition, two of the original questions were combined together due to their similarity. Hence, the validated risk identification tool contains three question groups, namely; Institutional, Societal, and Technical characteristics, including totally 54 quantified questions. Those three question groups determine the risk level of the prospective project.